ASEAN economic co-operation and challenges - Low, Linda (Institute of Southeast Asian Studies, 2004)
This book is written in an easily understood style. It explains the background of the origin of ASEAN (Association of Southeast Asian Nations) of which there are 10 member-countries. The author looks at the progress made, as well as the problems that the association faces